Identifikasi Fraksi Toksik Ekstrak Rumput Laut Eucheuma cottonii Lin - DIRA SWANTARA, I MADE (Indonesian Journal of Cancer, 2010)
Based on previous research, seaweed extract of Eucheuma sp was reported having antitumour activities. Eucheuma cottonii collected from Pari Island (Seribu archipelago) showed toxicity towards Artemia salina. Toxicity test using Artemia salina as bioindicator was a prescreening testing for anticancer agent. The aims of this research were to isolate and identify any potentially anticancer agent from the most toxic fraction of E. cottonii extract. Sample was extracted with 85 % ethanol using maceration method. The crude ethanol exract was then partitioned into n-hexane, chloroform, and ethyl acetate. The most active fraction towards artemia salina toxicity test was then purified using silica gel column chromatography with n-hexane:chloroform (2:3) as eluent. The pure active fraction having LC50 14.80 ppm was contitued of five compounds which identified using Gas Chromatography-Mass Spectrometry as Cyclododecana (3.23%), Tetradecanoic acid (7.10%), Hexadecanoic acid (54.74%), Cholesta-4,6-dien-3?-ol (6.67%), and Cholest-5-en-dien-3?-ol (Cholesterol) (28.26%).